1995
DOI: 10.1002/pd.1970150402
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and management of fetal agenesis of the corpus callosum

Abstract: Prenatal counselling for fetal agenesis of the corpus callosum is difficult as the prognosis until now has been so uncertain. We have reviewed the current world English literature to provide the best probabilistic information for prospective parents. In total, there are 70 cases where the diagnosis was made prenatally. The diagnosis of apparently isolated agenesis of the corpus callosum (in the absence of other sonographically detectable anomalies) appears to carry an excellent prognosis, with an 85 per cent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
61
1
9

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(74 citation statements)
references
References 42 publications
3
61
1
9
Order By: Relevance
“…[6][7][8][11][12][13][14][15] Interestingly, we did observe sulcation delay in many patients, including those with a good neurodevelopmental outcome, which suggests that the sulcation delay is actually a manifestation of the white matter dysgenesis that likely occurs in ACC, rather than a separate or additional abnormality. Longer term neurodevelopmental studies, however, are needed in these patients because developmental delays have been observed in children with prenatally diagnosed isolated ACC 7,10,12,34,35 and may not be detected until school age. 34 Our study is limited by the fact that fetal MR imaging was performed at many different gestational ages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][11][12][13][14][15] Interestingly, we did observe sulcation delay in many patients, including those with a good neurodevelopmental outcome, which suggests that the sulcation delay is actually a manifestation of the white matter dysgenesis that likely occurs in ACC, rather than a separate or additional abnormality. Longer term neurodevelopmental studies, however, are needed in these patients because developmental delays have been observed in children with prenatally diagnosed isolated ACC 7,10,12,34,35 and may not be detected until school age. 34 Our study is limited by the fact that fetal MR imaging was performed at many different gestational ages.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10] Although the prognostic implications of prenatally detected ACC are not fully understood, evidence suggests that the presence of additional brain abnormalities imparts a worse prognosis. [6][7][8][11][12][13][14][15] We chose to review our experience with cases of ACC and compare them with postnatal cohorts with ACC, to identify associated fetal brain abnormalities that may give insight into the etiology and outcome.…”
mentioning
confidence: 99%
“…40 Today, diagnosis relies on a midtrimester sonographic examination potentially revealing Յ1of the associated signs such as mild ventriculomegaly, colpocephaly, absent cavum septi pellucidi, upward displacement of the third ventricle, teardrop configuration of the lateral ventricles, or cystic dilation of the third ventricle. 25,26 However, these signs might be subtle or missing. 27,28 The presence of a normal CC and its biometry has been assessed by transabdominal and transvaginal 2D and 3D sonography and with fetal MR imaging from 18 weeks onward.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities of the CC are rarely isolated (Fig. 6) and because the presence of associated intra or extracranial anomalies determines the future neurodevelopmental outcome (38,39), it is important to detect them.…”
Section: Fig 5 a 33 Week Old Fetus With Severe Bilateral Asymmetric mentioning
confidence: 99%